2017
DOI: 10.1158/1078-0432.ccr-16-3261
|View full text |Cite
|
Sign up to set email alerts
|

First-in-Human Study of AMG 820, a Monoclonal Anti-Colony-Stimulating Factor 1 Receptor Antibody, in Patients with Advanced Solid Tumors

Abstract: Binding of colony-stimulating factor 1 (CSF1) ligand to the CSF1 receptor (CSF1R) regulates survival of tumor-associated macrophages, which generally promote an immunosuppressive tumor microenvironment. AMG 820 is an investigational, fully human CSF1R antibody that inhibits binding of the ligands CSF1 and IL34 and subsequent ligand-mediated receptor activation. This first-in-human phase I study evaluated the safety, pharmacokinetics, pharmacodynamics, and antitumor activity of AMG 820. Adult patients with rela… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
127
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(134 citation statements)
references
References 25 publications
6
127
1
Order By: Relevance
“…Indeed, we showed that both high HLA‐DP/DQ/DR expression and low numbers of TAMs are required to observe a beneficial effect in survival, as equal expression of both markers did not significantly affect DFS or DSS. Also, infiltration of TAMs are known to affect treatment responses in several tumor types and preclinical and clinical studies using anti‐CSFR1 Ab (macrophage colony‐stimulating factor receptor 1) have been performed . We, therefore, speculate that immunotherapy treatment targeting TAMs might be beneficial especially for patients with high expression of HLA‐DP/DQ/DR on tumor cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, we showed that both high HLA‐DP/DQ/DR expression and low numbers of TAMs are required to observe a beneficial effect in survival, as equal expression of both markers did not significantly affect DFS or DSS. Also, infiltration of TAMs are known to affect treatment responses in several tumor types and preclinical and clinical studies using anti‐CSFR1 Ab (macrophage colony‐stimulating factor receptor 1) have been performed . We, therefore, speculate that immunotherapy treatment targeting TAMs might be beneficial especially for patients with high expression of HLA‐DP/DQ/DR on tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Also, infiltration of TAMs are known to affect treatment responses in several tumor types 45 and preclinical and clinical studies using anti-CSFR1 Ab (macrophage colony-stimulating factor receptor 1) have been performed. [46][47][48] We, therefore, speculate that immunotherapy treatment targeting TAMs might be beneficial especially for patients with high expression of HLA-DP/DQ/ DR on tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Targeting or reeducating TAMs by inhibiting colony-stimulating factor 1 receptor (CSF-1R) showed suppression of GBM growth in mouse models 42 , but clinical trials with CSF-1R inhibitors failed to show signi cant e cacy for GBM patients 58 . Because CSF-1R is also expressed on circulating monocytes and other normal cells, targeting it resulted in serious toxic effects in the clinical trials 59 , making therapeutics targeting CSF-1R ineffective for clinical use 58,60 .…”
Section: Discussionmentioning
confidence: 99%
“…More recently, the evaluation of the safety, pharmacokinetics, pharmacodynamics, and antitumor activity of a fully human antibody against CSF1R (AMG 820) in a first-in-humans phase-I study for advanced solid tumors was published [ 62 ]. This study demonstrated that the anti-CSF1R antibody AMG 820 was tolerated with manageable toxicity up to 20 mg/kg every two weeks.…”
Section: Macrophage Targetingmentioning
confidence: 99%